Effects of Zn and A1 on corrosion characteristics of Sn-1.0Ag-0.5Cu alloys / Nurul Liyana Kamaruzaman - Nurul Liyana, Kamaruzaman (2018)
In the past few years, tin-lead (Sn-Pb) solder alloys had been popularly used in the electronic industries especially in packaging. However, lead and lead containing alloys have been banned because of environmental and health concerns. Recently, efforts are being made to develop a usable lead-free solder to substitute tin-lead based solder alloys. Comparing to other solders, tin-silver-copper (Sn-Ag-Cu) free solder alloys seem to be the best alternative to replace traditional lead-tin based solder alloys. In the present study, the corrosion characteristics of lead-free solder alloys such as Sn-1.0Ag-0.5Cu- XZn (X= 0, 0.1, 0.5. 1.0) and Sn-1.0Ag-0.5Cu-XAl (X=0, 0.1, 0.5, 1.0) have been investigated in 3.5wt-% NaCl solution. The corrosion behavior of were studied through Polarization curve and the Electrochemical Impedance Spectroscopy (EIS) by using Gamry Echem Analyst DC105 software. The microstructure and element of the corrosion compounds formed on the surface of lead-free solder alloys were investigated by Scanning Electron Microscopy (SEM), Energy-dispersive X-ray Spectroscopy (EDX), and X-ray Diffraction (XRD). The polarization curves showed that the addition of Zn in SAC105 solder alloy increased the corrosion current density and shifted the corrosion potential towards more negative values. As a result, the corrosion resistance of Sn-1.0Ag-0.5Cu-XZn alloys reduces with the increase of Zn concentration. The EIS results agreed well with the findings obtained from polarization curves. The corrosion products at the surface of the investigated Zn doped alloys constituted of Sn3O(OH)2Cl2, SnO, SnO2 and ZnO. Like Zn, addition of Al also decreases the corrosion resistance of the SAC 105 solder alloy